2010
DOI: 10.1021/ja100265j
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bis(imidazolidine)pyridine−Cu(OTf)2: Catalytic Asymmetric Endo-Selective [3 + 2] Cycloaddition of Imino Esters with Nitroalkenes

Abstract: The novel C(2)-symmetric bis(imidazolidine)pyridine (PyBidine) ligand was easily synthesized in a single condensation of 2,6-pyridyl aldehyde and optically active (S,S)-diphenylethylenediamine. In the C(2)-symmetric PyBidine-Cu(OTf)(2) complex, imidazolidine rings act as "chiral fences" to shield the first and third quadrants. Use of the PyBidine-Cu(OTf)(2) complex as a catalyst enabled the highly endo-selective reaction of imino esters and nitroalkenes to give the adducts in up to 99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(58 citation statements)
references
References 46 publications
1
56
0
1
Order By: Relevance
“…[2] Despite excellent results achieved for this transformation, most dipolarophiles applied in these reactions are mono-activated or symmetrically double-activated, electron-deficient alkenes. [3][4][5][6][7][8] However, unsymmetrically 1,2-disubstituted alkenes with two different electron-withdrawing groups have been seldom studied in the catalytic 1,3-dipolar cycloaddition, probably owing to the synthetic challenges associated with the regio-, enantio-and diastereoselectivity. Recently, an excellent result was achieved by Carretero and co-workers when employing unsymmetrically 1,2-diactivated (Z)-sulfonyl acrylate as the dipolarophile and Cu I /(R)-Segphos complex as the catalyst.…”
mentioning
confidence: 99%
“…[2] Despite excellent results achieved for this transformation, most dipolarophiles applied in these reactions are mono-activated or symmetrically double-activated, electron-deficient alkenes. [3][4][5][6][7][8] However, unsymmetrically 1,2-disubstituted alkenes with two different electron-withdrawing groups have been seldom studied in the catalytic 1,3-dipolar cycloaddition, probably owing to the synthetic challenges associated with the regio-, enantio-and diastereoselectivity. Recently, an excellent result was achieved by Carretero and co-workers when employing unsymmetrically 1,2-diactivated (Z)-sulfonyl acrylate as the dipolarophile and Cu I /(R)-Segphos complex as the catalyst.…”
mentioning
confidence: 99%
“…The authors justified these results on the basis of a concerted mechanism, where the negative charge of the nitro group interacted with the copper atom. This hypothesis was not confirmed for any theoretical study until date [57].…”
Section: Chiral Copper Complexes As Catalystsmentioning
confidence: 79%
“…The [3+2] cycloaddition reaction of azomethine ylide with olefinic dipolarophiles constitutes a straightforward approach to the synthesis of highly substituted chiral pyrrolidine derivatives. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] So far, many laboratories have reported the catalytic asymmetric [3+2] cycloadditions with azomethine ylides by means of a variety of ligand-metal combinations. Our group reported that the ferrocenyloxazoline derived chiral N,P ligand showed excellent performance in the Ag(I)-catalyzed enantioselective 1,3-dipolar cycloaddition of azomethine ylides.…”
Section: Resultsmentioning
confidence: 99%